Creative lighting : digital photography tips & techniques - Davis, Harold , 1953- (Wiley Publishing, 2011)
Offers advice on using lighting to enhance a subject and the final picture, covering such topics as the exposure, natural lighting, ambient light, and enhancing lighting effects